Extensive phenotypic diversity in the cultivated Florist's Gloxinia, Sinningia speciosa (Lodd.) Hiern, is derived from the domestication of a single founder population. Issue 4 (19th August 2019) - Hasing, Tomas; Rinaldi, Elijah; Manrique, Silvia; Colombo, Lucia; Haak, David C.; Zaitlin, David; Bombarely, Aureliano
Societal Impact Statement: Domesticated plants are essential for agriculture and human societies. Hence, understanding the processes of domestication will be crucial as we strive for more efficient crops and improvements to plants that benefit humankind in other ways. Here, we study the ornamental plant Sinningia speciosa, and reveal that despite the incredible variety found in domesticated varieties (e.g., in flower colour and form), they are all derived from a single founder population near Rio de Janeiro, Brazil. Knowledge of the domestication of horticultural plants is scarce and given its small, low‐complexity genome, and ease of cultivation, we suggest that S. speciosa is a good model for studying genomic variation during domestication. Summary The process of domestication often involves a complex genetic structure with contributions from multiple founder populations, interspecific hybridization, chromosomal introgressions, and polyploidization events that occurred hundreds to thousands of years earlier. These complex origins complicate the systematic study of the sources of phenotypic variation. The Florist's Gloxinia, Sinningia speciosa (Lodd.) Hiern, was introduced into cultivation in England two hundred years ago from botanical expeditions that began in the 18th century. Since that time, amateur plant breeders and small horticultural companies have developed hundreds of cultivars with a wide range of flower colors and shapes. In our genetic study of S. speciosa, we examined an extensive diversity panel consisting of 115 individuals that included different species, wild representatives, and cultivated accessions. Our analysis revealed that all of the domesticated varieties are derived from a single founder population that originated in or near the city of Rio de Janeiro in Brazil. We did not detect any major hybridization or polyploidization events that could have contributed to the rapid increase in phenotypic diversity. Our findings, in conjunction with other features such as a small, low‐complexity genome, ease of cultivation, and rapid generation time, makes this species an attractive model for the study of genomic variation under domestication. Abstract : Domesticated plants are essential for agriculture and human societies. Hence, understanding the processes of domestication will be crucial as we strive for more efficient crops and improvements to plants that benefit humankind in other ways. Here, we study the ornamental plant Sinningia speciosa, and reveal that despite the incredible variety found in domesticated varieties (e.g., in flower colour and form), they are all derived from a single founder population near Rio de Janeiro, Brazil. Knowledge of the domestication of horticultural plants is scarce and given its small, low‐complexity genome, and ease of cultivation, we suggest that S. speciosa is a good model for studying genomic variation during domestication.